Three-dimensional Laparoscopic Management of a Large Prostatic Utricle Cyst in a 6-month-old Boy: An Efficient Minimally Invasive Approach - Animesh; Vinay Shelke; Abhishek Tiwari; Himanshu Acharya; Vikesh Agrawal (Journal of Indian Association of Pediatric Surgeons)
Prostatic utricle cysts (PUCs) in males with normal external genitalia are rare and often asymptomatic. Minimally invasive surgical techniques, such as laparoscopic excision, have demonstrated effectiveness for symptomatic cases. This report highlights the advantages of a three-dimensional (3D) laparoscopic approach in managing a large PUC in a 6-month-old boy. A 6-month-old male presenting with urinary obstruction and recurrent infections underwent diagnostic imaging and isotope renography, revealing a large PUC with associated nonfunctioning right ectopic kidney and ureter opening in the cyst. A 3D laparoscopic excision of the cyst and associated structures was performed, followed by orchiopexy for the right intra-abdominal testis. The surgery was completed successfully in 70 min without complications. Postoperative recovery was uneventful, with the patient symptom-free during 2 years of follow-up. 3D laparoscopy offers superior visualization and ergonomics compared to traditional two-dimensional laparoscopy, making it a preferred option for complex pediatric pelvic surgeries. This case underscores its advantages in safety, efficiency, and surgical outcomes, especially in centers where robotic surgery may not be available at present.